ID: 7. Issue 4 (April 2016) - Jetty, V; Prince, M; Wang, P; Glueck, CJ
Abstract : Background: Traditionally, elective knee arthroscopy has been thought to be an unlikely source of venous thromboembolic events (VTE) (0.6% to 18%) in contrast to total knee replacement (TKR) with incidence of ∼30%. Hence, there have been no guidelines for thromboprophylaxis in elective, routine knee arthroscopy. Purpose: In 10 patients with VTE after routine knee arthroscopy, our specific aim was to assess for familial and acquired thrombophilia, with contrast to 110 healthy normal controls and 17 patients after total hip and knee replacement (THKR). Methods: Patients were included if they had a VTE up to 6 months after either knee arthroscopy or THKR. In these patients, we measured Factor V Leiden, Prothrombin gene mutation (PTG), Plasminogen activating inhibitor gene (PAI-G) mutation, methylenetetrahydrofolate reductase (MTHFR) mutations, elevated Factors VIII and XI elevated homocysteine, Anticardiolipin IgG and IgM antibodies, Lupus anticoagulant, antigenic protein C, S (and free S), and antithrombin III deficiency. The same coagulation data was obtained for normal controls (n=110) and for 17 patients who had VTE after TKHR. Results: As summarized below, the major thrombophilias in the arthroscopy group were Factor V Leiden heterozygosity in 40%, high factor VIII in 50%, and high homocysteine in 30%. This pattern in the 10 patients with arthroscopy did not differ from that in 17 patients with THKR, who also differed from normal by having more frequent low proteins C and S. Conclusion: Although VTE after knee arthroscopy is uncommon, we suggest that three common familial thrombophilias Factor V Leiden, high Factor VIII, and homocysteine routinely be measured before arthroscopy to facilitate post arthroscopy thromboprophylaxis.